L-SIGN is a receptor on liver sinusoidal endothelial cells for SARS-CoV-2 virus - Kondo, Yuji; Larabee, Jason L.; Gao, Liang; Shi, Huiping; Shao, Bojing; Hoover, Christopher M.; McDaniel, J. Michael; Ho, Yen-Chun; Silasi-Mansat, Robert; Archer-Hartmann, Stephanie A.; Azadi, Parastoo; Srinivasan, R. Sathish; et al. (JCI insight, 2021)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains a pandemic. Severe disease is associated with dysfunction of multiple organs, but some infected cells do not express ACE2, the canonical entry receptor for SARS-CoV-2. Here, we report that the C-type lectin receptor L-SIGN interacted in a Ca2+-dependent manner with high-mannose–type N-glycans on the SARS-CoV-2 spike protein. We found that L-SIGN was highly expressed on human liver sinusoidal endothelial cells (LSECs) and lymph node lymphatic endothelial cells but not on blood endothelial cells. Using high-resolution confocal microscopy imaging, we detected SARS-CoV-2 viral proteins within the LSECs from liver autopsy samples from patients with COVID-19. We found that both pseudo-typed virus enveloped with SARS-CoV-2 spike protein and authentic SARS-CoV-2 virus infected L-SIGN–expressing cells relative to control cells. Moreover, blocking L-SIGN function reduced CoV-2–type infection. These results indicate that L-SIGN is a receptor for SARS-CoV-2 infection. LSECs are major sources of the clotting factors vWF and factor VIII (FVIII). LSECs from liver autopsy samples from patients with COVID-19 expressed substantially higher levels of vWF and FVIII than LSECs from uninfected liver samples. Our data demonstrate that L-SIGN is an endothelial cell receptor for SARS-CoV-2 that may contribute to COVID-19–associated coagulopathy.